A Comparison of Hand Grip Strength Among Healthy Young Adult Malaysian and Thai Women - Isa Halim; Radin Zaid Radin Umar; Zulkeflee Abdullah; Muhammad Syafiq Syed Mohamed; Seri Rahayu Kamat; Mohd Shukor Salleh; Dujdow Buranapanichkit; Kunlapat Thongkaew; Ezrin Hani Sukadarin; Denni Kurniawan; Adi Saptari (Jurnal Optimasi Sistem Industri, 2026)
Hand grip strength (HGS) is a well-known parameter of physical capability, clinical health status, and functional work performance. However, the scarcity of standardized, region-specific HGS data for Southeast Asian populations restricts the accuracy of health screening practices and the development of ergonomics and occupational safety guidelines. The aim of this study was to measure the dominant-hand HGS for healthy young adult women of Malaysia and Thailand, to compare the HGS of these two groups of women, and to investigate the relationship between age and anthropometric variables and the HGS. Researchers conducted a cross-sectional study involving 166 healthy women aged 20 to 39 years. This study recruited 92 participants from Malaysia and 74 from Thailand, primarily from university students and staff populations. Dominant-hand HGS was measured using a Jamar dynamometer (Sammons Preston, USA) while participants adopted a standardized standing position with the forearm in a neutral posture. Thai women demonstrated significantly greater mean HGS than Malaysian women (27.31 ± 6.96 kg vs. 23.64 ± 4.67 kg; p < 0.001), corresponding to an approximately 16% difference and a medium-to-large effect size (Cohen’s d = 0.63). Among Thai participants, HGS was significantly associated with palm circumference (r = 0.544), height, weight, and age. These variables collectively explained 44.8% of the variation in HGS. In contrast, only height showed a modest association with HGS among Malaysian participants. Meanwhile, the corresponding regression model demonstrated limited explanatory capability. These findings reveal population-specific differences in both HGS and its anthropometric correlates when assessed under standardized testing conditions. The study provides protocol-specific, preliminary reference data for healthy young adult Malaysian and Thai women, which may inform future development of validated, population-specific reference standards. By generating population-specific reference data, this study contributes to improving the accuracy and equity of health monitoring practices, in line with the objectives of United Nations SDG 3 (Good Health and Well-being).